Phenethylamine@Pillar[5]arene Biointerface for Highly Enantioselective Adsorption of Protein. Issue 7 (5th March 2020) - Yan, Hewei; Ma, Junkai; Zhu, Fei; Quan, Jiaxin; Dhinakaran, Manivannan Kalavathi; Li, Haibing
Abstract: In the life system, the biointerface plays an important role in cell adsorption, platelet adsorption and activation. Therefore, the study of protein adsorption on the biointerface is of great significance for understanding life phenomena and treatment in vitro. In this paper, a chiral biointerface was constructed by the virtue of host‐guest interaction between a water‐soluble pillar[5]arene (WP5) and phenethylamine (PEA) over a gold surface for adsorption of lysozyme proteins. From the experimental results it was identified that the host‐guest biointerface has a high adsorption capacity and strong chiral selectivity. Furthermotre, it was identified that the host‐guest interaction plays the decisive role in the enhancement of chirality of the interface, which was much beneficial for increasing protein adsorption and amplifying the capacity of chiral discrimination. Therefore, this work provides a new idea for the construction of biointerface materials with high protein adsorption capacity and high chiral selectivity through supramolecular interaction, which will have potential applications in the fields of biosensors, biocatalysts, biomaterials. Abstract : The study of protein adsorption on a biointerface is of great significance for understanding life phenomena and treatment in vitro. In this paper, a chiral biological interface was constructed by the strategy of interaction between host and guest for the adsorption of lysozyme proteins. Host‐guest interfaces with stronger chirality have stronger chiral selectivity.